2003
DOI: 10.1034/j.1600-9657.2003.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously healed root fracture: report of a case

Abstract: Blows to the facial region can cause root fractures especially in anterior teeth. Fractures below the alveolar crest have a very high potential for healing and treatment consists of reduction and rigid splinting immediately after trauma. The aim of the treatment is to obtain reunion of the fragments. Although the fracture can heal spontaneously, the prognosis will not be as good as the correctly treated ones. The purpose of this paper is to report a case of spontaneously healed root fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…The healing of root fractures with or without initial treatment is reported to occur in up to 80% of cases, whereas pulp necrosis occurred in 20% (23)(24)(25). When the fracture line allows communication with the oral cavity, immobilization is difficult, and microbial contamination of the pulp with subsequent pulpal necrosis is almost inevitable (4,7).…”
Section: Discussionmentioning
confidence: 97%
“…The healing of root fractures with or without initial treatment is reported to occur in up to 80% of cases, whereas pulp necrosis occurred in 20% (23)(24)(25). When the fracture line allows communication with the oral cavity, immobilization is difficult, and microbial contamination of the pulp with subsequent pulpal necrosis is almost inevitable (4,7).…”
Section: Discussionmentioning
confidence: 97%
“…A root-fractured tooth without displacement has a higher likelihood of maintaining its vitality than a displaced tooth. 6 Andreasen et al 7 showed that optimal repositioning of root fractures with dislocation of the coronal segment of up to 1 mm favored both healing with hard tissue and at the same time reduced the risk of pulp necrosis. In addition, it is generally accepted that roots with incomplete root formation have a greater potential for maintaining pulp vitality than those with closed apices.…”
Section: Discussionmentioning
confidence: 99%
“…Repair appears to depend on an intact periodontal ligament, from which the hard tissue forming cells originate [4]. However, healing of root fractures without treatment is also presented in many reports [12,13,15]. In traumatic injuries, follow-up is of critical importance [16].…”
Section: Discussionmentioning
confidence: 99%